Latin America in graphs: demographic and economic trends 1972-1992 (Inter-American Development Bank Washington, D.C.US, 1993)
Contains a selection of graphs for each of the 26 developing member countries of the Inter-American Development Bank as well as for four economic regions and for Latin America. Represents trends in important demographic and economic variables over the period 1972-1992.
DC